Visualisation of HIFU lesions using elastography of the human prostate in vivo: preliminary results - Souchon, Rémi; Rouvière, Olivier; Gelet, Albert; Detti, Valérie; Srinivasan, Seshadri; Ophir, Jonathan; Chapelon, Jean Yves (Ultrasound in medicine & biology, 2003)
An imaging system was developed for prostate elastography in vivo using a transrectal ultrasound (US) probe to guide high-intensity focused US (HIFU) therapy of prostate cancer. Uniform compression was applied using a balloon, while a sector image was acquired. Strain was calculated from the gradient of the displacements obtained from the ultrasonic signal using the cross-correlation technique. Elastograms were acquired on a total of 31 patients undergoing HIFU therapy for localised prostate cancer. For two patients, only part of the prostate was treated and posttherapy magnetic resonance imaging (MRI) confirmed the size and position of the HIFU lesions seen in the elastograms as low strain areas, with a strain contrast ratio between 1.6 and 3.2. The whole prostate was treated for the next 29 patients. After treatment, the whole prostate appeared to be stiff in the elastograms and a 40% to 60% (mean 50%) decrease in average strain was observed when compared to strains measured before HIFU application. Tumours identified by biopsies and sonograms could occasionally be seen in the preoperative elastograms. Decorrelation effects occurred mainly because of low sonographic signal-to-noise ratio (SNR) and of out-of-plane motion induced by respiration.